Loopbaanontwikkeling in verhouding tot bedryfsmaatskaplikewerk : 'n teoretiese fundering (Afrikaans) - Kasselman, Joachim Petrus Hermanus (2013)
The full text of this thesis/dissertation is not available online. Pending permission from the author/supervisor access may be provided on request. Read the abstract in the section 00front of this document. === Thesis (D Phil (Social Work))--University of Pretoria, 2007. === Social Work and Criminology === Unrestricted